Management of B-cell lineage acute lymphoblastic leukemia: expert opinion from an Indian panel via Delphi consensus method - Mathews, Vikram; Korula, Anu; Chakrapani, Anupam; Bhurani, Dinesh; Bhattacharyya, Jina; Sengar, Manju; Malhotra, Pankaj; Boyella, Pavan Kumar; Singh, Pawan Kumar; Ganesan, Prasanth; Dhawan, Rishi; Melinkeri, Sameer; et al. (Frontiers in Oncology, 2023)
Abstract Introduction: Currently, there are no guidelines for the management of B-cell lineage acute lymphoblastic leukemia (B-ALL) from an Indian perspective. The diagnostic workup, monitoring, and treatment of B-ALL vary among different physicians and institutes. Objective: To develop evidence-based practical consensus recommendations for the management of B-ALL in Indian settings. Methods: Modified Delphi consensus methodology was considered to arrive at a consensus. An expert scientific committee of 15 experts from India constituted the panel. Clinically relevant questions belonging to three major domains were drafted for presentation and discussion: (i) diagnosis and risk assignment; (ii) frontline treatment; and (iii) choice of therapy (optimal vs. real-world practice) in relapsed/refractory (R/R) settings. The questionnaire was shared with the panel members through an online survey platform. The level of consensus was categorized into high (≥80%), moderate (60%–79%), and no consensus (<60%). The process involved 2 rounds of discussion and 3 rounds of Delphi survey. The questions that received near or no consensus were discussed during virtual meetings (Delphi rounds 1 and 2). The final draft of the consensus was emailed to the panel for final review. Results: Experts recommended morphologic assessment of peripheral blood or bone marrow, flow cytometric immunophenotyping, and conventional cytogenetic analysis in the initial diagnostic workup. Berlin–Frankfurt–Münster (BFM)–based protocol is the preferred frontline therapy in pediatric and adolescent and young adult patients with B-ALL. BFM/German Multicenter Study Group for Adult Acute Lymphoblastic Leukemia–based regimen is suggested in adult patients with B-ALL. Immunotherapy (blinatumomab or inotuzumab ozogamicin) followed by allogeneic hematopoietic cell transplantation (allo-HCT) is the optimal choice of therapy that would yield the best outcomes if offered in the first salvage in patients with R/R B-ALL. In patients with financial constraints or prior allo-HCT (real-world practice) at first relapse, standard-intensive chemotherapy followed by allo-HCT may be considered. For subsequent relapses, chimeric antigen receptor T-cell therapy or palliative care was suggested as the optimal choice of therapy. Conclusion: This expert consensus will offer guidance to oncologists/clinicians on the management of B-ALL in Indian settings.